Rasio Lendutan Geser terhadap Lendutan Lentur dan Pengaruhnya terhadap Kekakuan Lentur (EI) pada Balok Kayu Ratio of Shear to Bending Deflection and Its Influence to Bending Stiffness (EI) of Timber Beam - Indah Sulistyawati (Jurnal Ilmu dan Teknologi Kayu Tropis, 2006)
Bending Stiffness values which is expressed in EI can be obtained by using bending test of beam in laboratory. Base on value of deflection that was entered to one particular equation, can be calculated the bending stiffness. Usually bending test in laboratory was conducted with beam put down above two simple placements by giving one point loading in the middle span or two points loading in one-third span each. The deflection was measured in the middle of span. In the calculation of bending stiffness, usually used the deflection of the bending moment only. In fact, there was deflection caused by shear load, so total deflection in the middle span is bending deflection plus shear deflection. The shear deflection on beams with certain length and dimension was compared to bending deflection that has different value to each other. The test of Acacia mangium timber beam showed that comparison value has variety; it can reach more than 15%. This matter will influence the value of the bending stiffness of beam. By including shear deflection higher bending stiffness value will be obtained, so it will yield more economical design.The objective of this research was to determine ratio of shear to bending deflection, and the influence of calculation of bending stiffness if shear deflection on the beam with certain dimension and length of span is calculated.